"Meth Mouth": An Interdisciplinary Review of a Dental and Psychiatric Condition. Issue 4 (July 2017) - Stanciu, Cornel N.; Glass, Magdalena; Muzyka, Brian C.; Glass, Oliver M.
Abstract : Objective: Chronic methamphetamine (MA) users experience many dental problems, a condition characterized as "meth mouth." These devastating effects on dentition is the main reason why many seek professional help. Here, we discuss the effects of MA on oral health and advocate for improved collaboration between dentists and mental health providers. We also introduce a dental evaluation tool with the goal of improving the quality of care for this often-marginalized patient population. Methods: A Medline literature search (1985–2016) was conducted with keywords "meth mouth, " "methamphetamine AND oral health"; "methamphetamine AND dental"; "methamphetamine AND dentist." Results were supplemented by references gleaned from recent reviews, credible online sources, and citations of search returns. Results: MA predisposes users to tooth decay. They are also more likely to have missing dentition with a linear relationship correlating the number of years of use. A constellation of dental symptoms resulting from chronic MA use has been described in literature: gingival inflammation, excessive tooth wear, decreased salivary output, and severe dental caries. With continued use, mucosal lesions may appear on the lips and the gingival tissue may recede. MA can trigger bruxism, resulting in severe wear patterns and even cracked teeth. Conclusions: Users of MA have many unmet medical and mental health needs. An interdisciplinary approach between dentists and mental health providers can improve outcomes. The dental evaluation tool described here can improve the bidirectional collaboration between mental health and dentistry. Dental professionals are in a unique position to identify users and can facilitate referral to substance abuse treatment. Likewise, mental health providers can identify, assess severity, and prompt users for medical and dental attention.